Impact of Various Land Uses and Soil Depths on Physicochemical Characteristics of Lateritic Soils of Bankura, West Bengal, India - Singha, Subhajit; Dutta, Subhajit; Kundu, M. C. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during 2015–16 (November 2015-April 2016) at the Bankura district of West Bengal, India to assess the impact of land uses of Bankura on soil properties by sampling and analyzing soils from diverse representative plots from forests, orchards, pastures, cultivated fields, and uncultivated fallow lands that existed over the last decade. The average bulk density was highest at 1.38 g cm-3 in orchard land and lowest at 1.24 g cm-3 in pasture land, and increased with depth. The mean particle density varied from 2.53 g cm-3 in pasture to 2.69 g cm-3 in orchard, and also increased with depth. The total porosity was maximum in orchard (53.97%) and minimum in pasture (45.57%), and varied with depth. Moisture content was greatest in cultivated land (8.98%) and least in pasture (4.23%), whereas mean maximum water holding capacity was greatest in forest land (37.11%) and least in fallow land (29.05%), and both rose with depth. Soil pH was greatest in pasture (6.75) and least in cultivated land (5.61), and electrical conductivity was similarly distributed. Organic carbon content was greatest in forest land (0.41%) and least in cultivated land (0.16%), and decreased with depth. Available nitrogen, phosphorus, and potassium content were greatest in forest land and lowest in cultivated land, and decreased with an increase in soil depth. Pearson's correlation revealed significant correlations between soil properties.